THE LISTENER OF THE PROFESSIONAL EDUCATION SYSTEM STAFF PROFESSIONAL COURSE - Nazirova Minavar Anarbekovna (Лучшие интеллектуальные исследования, 2024)
Abstract: In this electronic qualification work, the focus is on investigating how Total Physical Response (TPR), a pedagogical approach that incorporates physical movements and gestures into language instruction, can effectively enhance learning experiences for young learners.